Adaptive-fuzzy Pid controller for antilock braking system utilizing electronic cone wedge brake - Haris, Sharil Izwan (2024)
The prevalence of accidents resulting from vehicle braking failures has led to advancements in active safety technology, resulting in the development of brake-by-wire (BBW) systems, which completely revamp conventional braking mechanisms. Due to the need for high braking torque and quick response within a 12 V power source, BBW systems now increasingly integrate electronic wedge brake (EWB) technology. This study aims to develop and optimize a new EWB mechanism to reduce power consumption, validate its mathematical model, and evaluate its performance in a hardware-in-the-loop-simulation (HILS) environment. Additionally, the study seeks to assess the effectiveness of the proposed anti-lock braking system (ABS) controller in maintaining desired tire slip during braking, using the optimized EWB as the brake actuator. To achieve these, two evaluation methods were employed namely the MATLAB Simulink program and HILS methodology. In the simulation investigation, both the validated quarter vehicle traction model and the CW-EWB actuation model were utilized to simulate the vehicle's braking system. Afterwards, the braking system's performance was assessed using dynamic tests that simulated sudden braking conditions at 40 km/h and 60 km/h and verified through HILS experiments conducted on a test rig. Brake performance, such as vehicle body speed, wheel speed, longitudinal slip and stopping distance, are the parameters evaluated. Moreover, the validated CW-EWB system was further integrated with the ABS. The developed ABS control mechanism was incorporated into the CW-EWB model utilizing conventional PID and self-tuning PID control strategies, namely Fuzzy Logic PID (FPID) and Self-Tuning Fuzzy PID (SFPID). These control techniques were compared and evaluated in dynamic simulation tests. The findings reveal that SFPID is the most efficient ABS control technique compared to PID and FPID, as it is 10 % and 1 % faster in stopping time, 8 % and 1 % shorter in stopping distance, 9 % and 1 % faster in settling time, and 40 % and 5 % more efficient in achieving the target slip, respectively. For future work, ABS evaluation must be measured to confirm the prediction from the ABS control technique. Experiments on actual vehicles are also required to replace the HILS test method in order to analyze the brake system's performance more precisely.